2010
DOI: 10.3109/15622975.2010.483251
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of SCOFF questionnaire for screening of eating disorders among adults

Abstract: This study demonstrates that the French version of SCOFF questionnaire is accurate and reliable for the detection of women with EDs in this high-risk student population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 23 publications
(29 reference statements)
1
65
1
2
Order By: Relevance
“…We compared the mean results in the two gender groups by Mann-Whitney test and found significant differences (p < 0.001). Two "yes" responses from the SCOFF questionnaire defined the threshold for indicating 100% sensitivity to anorexia and bulimia (Garcia et al, 2010;Morgan, Reid, & Lacey, 1999). These results meant that one third of all the respondents could be considered at high risk of having or developing an ED.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We compared the mean results in the two gender groups by Mann-Whitney test and found significant differences (p < 0.001). Two "yes" responses from the SCOFF questionnaire defined the threshold for indicating 100% sensitivity to anorexia and bulimia (Garcia et al, 2010;Morgan, Reid, & Lacey, 1999). These results meant that one third of all the respondents could be considered at high risk of having or developing an ED.…”
Section: Resultsmentioning
confidence: 83%
“…These results meant that one third of all the respondents could be considered at high risk of having or developing an ED. Garcia et al (2010) found 54 (13.5%) respondents with two positive answers, using a French version of the SCOFF questionnaire in 400 undergraduate female students. Of these, 35 had typical ED and 19 were false positives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCOFF is an eating disorder screening questionnaire [22] comprising essential characteristics of anorexia and bulimia nervosa [23].…”
Section: Bulgarian Version Of the Scoffmentioning
confidence: 99%
“…Two positive answers to SCOFF items are a sensitive cutoff used to classify the groups at risk for anorexia and bulimia [22,23,25].…”
Section: Scalesmentioning
confidence: 99%